Impact on Inpatient Length of Stay in Adults with Deep Partial-Thickness Burns: Comparing the Bioengineered Allogeneic Cellularized Construct Expanded-Access Trial with National Burn Repository Data - Yu TC; Hahn H; Rutan R; Hu FS; Zheng Z (Dove Medical Press, 2024)
Tzy-Chyi Yu,1 Helen Hahn,2 Randi Rutan,2 Feng-Sheng Hu,3 Zhishui Zheng3 1Health Economics and Outcomes Research, Mallinckrodt Pharmaceuticals, Bridgewater, NJ, USA; 2Clinical Development and Medical Affairs, Mallinckrodt Pharmaceuticals, Bridgewater, NJ, USA; 3Health Economics and Outcomes Research, KMK Consulting, Inc, Morristown, NJ, USACorrespondence: Tzy-Chyi Yu, HEOR, Regenerative Medicine, Mallinckrodt Pharmaceuticals, 440 Route 22 East, Suite 302, Bridgewater, NJ, 08807, USA, Email tzychyiyu@hotmail.comPurpose: To investigate the effect of StrataGraft (bioengineered allogeneic cellularized construct [BACC]) treatment on inpatient length of stay (LOS) as an indicator of hospital resource utilization.Patients and Methods: Data from the single-arm StrataCAT trial for adult patients with deep partial-thickness (DPT) burns who received BACC were compared with data from a matched external control arm comprising patients who received autografting for burn treatment from the National Burn Repository (NBR) during the same time period as StrataCAT. A matching, quasi-experimental approach was used to investigate the cause-and-effect relationship between BACC treatment and LOS (days). Matching factors included sex, age, ethnicity, race, burn causes, %TBSA burned (third-degree), %TBSA burned (second- and third-degrees), inhalation injury, diabetes mellitus, and hypertension. Balance was assessed between the cohorts for each confounder by standardized mean differences (SMD). Outcome was reported as average treatment effect on the treated.Results: The BACC and NBR Autograft cohorts included 47 and 2641 patients, respectively. Following matching, the Autograft cohort had 137 patients and was weighted to 47 patients. Patients in the BACC and final (matched) Autograft cohorts were similar in all demographic and clinical covariate categories after matching (ie, the absolute SMD were < 0.1). Treatment with BACC reduced the inpatient LOS by an average of 4.84 days (P = 0.0127) relative to the comparable (matched) Autograft cohort. An ad hoc analysis revealed that mean [SD] LOS for BACC and the weighted Autograft cohorts were 17.68 [12.75] and 22.51 [19.75] days, respectively, and were 1.39 [0.94] and 1.88 [1.31] days per %TBSA burned, respectively.Conclusion: The significantly reduced inpatient LOS observed with BACC compared to Autograft in adults with DPT burns may translate into reduced burden on the healthcare system, reduced costs for inpatient burn treatment, and clinical benefits for patients.Keywords: deep partial-thickness burns, severe burns, length of stay, National Burn Repository, bioengineered allogeneic cellularized construct